Mechano-responsive polymer solutions based on CO2 supersaturation: shaking-induced phase transitions and self-assembly or dissociation of polymeric nanoparticles - Roth, Peter; Quek, J.; Zhu, Y.; Blunden, B.; Lowe, A. (The Royal Society of Chemistry, 2014)
Mechanical stimulation of supersaturated aqueous CO2 solutions is accompanied by a pH increase within seconds. In solutions of tailored homo- and AB diblock copolymers this is exploited to induce micelle formation, or, taking advantage of an aqueous upper critical solution temperature transition, nanoparticle disassembly.